2013
DOI: 10.3126/nepjoph.v5i2.8727
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography in diabetic macular edema: patterns and related risk factors

Abstract: Introduction: Diabetic Macular Edema (DME) is an important cause of vision loss in diabetic retinopathy. Optical Coherence Tomography (OCT) is a non-invasive modality that produces high-resolution images of retinal layers. Objective: To evaluate the prevalence of DME patterns and their association with risk factors and visual acuity. Materials and Methods: In this cross-sectional study, type 2 diabetics with macular edema referred to our center during a ten-month period underwent OCT. Patients with macular ede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…OCT offers a high resolution image of a limited area. Since OCT uses light to acquire images, its use is limited by media opacities [5,6].…”
Section: Display 2d 3dmentioning
confidence: 99%
See 2 more Smart Citations
“…OCT offers a high resolution image of a limited area. Since OCT uses light to acquire images, its use is limited by media opacities [5,6].…”
Section: Display 2d 3dmentioning
confidence: 99%
“…It offers qualitative information on retinal thickness, and it is reliable and reproducible. OCT reveals the presence and extension of vitreo-macular traction (VMT) [5,6].…”
Section: Display 2d 3dmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the article by Ahmadpour-Baghdadabad M et al (2013) in which the authors studied the association of various patterns of diabetic macular edema (DME) with the risk factors of DME based on the optical coherence tomography (OCT) findings.…”
Section: Dear Editormentioning
confidence: 99%
“…
We read with interest the article by Ahmadpour-Baghdadabad M et al (2013) in which the authors studied the association of various patterns of diabetic macular edema (DME) with the risk factors of DME based on the optical coherence tomography (OCT) findings.In a retrospective cross-sectional study, we too evaluated the systemic risk factors associated with sub-retinal fluid (SRF) pattern of DME. We compared 37 eyes with SRF pattern of DME (designated cases) versus 30 eyes having DME (sponge like retinal swelling or cystoid macular edema) without SRF (designated controls) on spectral domain-OCT. We too found that the SRF pattern was more common in males than in females (84.8 % of cases were males versus 66.7 % of controls).
…”
mentioning
confidence: 99%